The use of graph-theoretical models to evaluate two electroanalytical methods for determination of stability constants - Raos, Nenad (Array, 2008)
Summary: Stability constants K1 and b2 of copper(II) complexes with alanine and its five N-alkylated and N,N-dialkylated derivatives were measured by glass electrode potentiometry (GEP) and square wave voltammetry (SWV) and evaluated using graph-theoretical models. Correlations with the connectivity index of the 3rd order, 3cv, show that log K1(GEP) values were better reproduced than log K1(SWV) values; S.E. = 0.18–0.16 vs. 0.29–0.35, respectively. The opposite is true for log b2 (S.E. = 0.51–0.56 vs. 0.39–0.47 for GEP and SWV, respectively). By applying three criteria – 1) difference between GEP and SWV values, 2) difference between SWV and theoretical values, and 3) correlation of experimental error (S.E.exp) to the difference between experimental and theoretical values – it was possible to determine three experimental log K1(SWV) values as problematic. This report demonstrates the value of recently developed graph-theoretical models in planning the experiments and discussing their results